Sloppy organisms - Giuliani, Alessandro (Organisms. Journal of Biological Sciences, 2017)
Commentary on: Transtrum M.K. et al., 2015, Perspective: Sloppiness and emergent theories in physics, biology and beyond, The Journal of Chemical Physics. Vol. 143: 01091.